Grafomotricidad y su aporte en la lectoescritura a estudiantes de la unidad educativa “león de Febres Cordero”, Parroquia San Juan, cantón Puebloviejo, Provincia los Ríos - Botto Peralta, Solvia María (2016)
The graphomotor is important because during the preschool stage different motor skills are developed, which play a major role in the acquisition process of writing and reading. During this period, among the five years it is when these are strengthened and it is the duty of the teacher help the child to properly develop skills that allow you to learn to read and write. One is the graphomotor, that aims to analyze the processes involved in the realization of the graphs. The spelling is the stroke resulting from a movement, if an individual is able to repeat the stroke in the same way it is because it has internalized. In the embodiment of the graphs we find the incidence of cognitive, affective and psychomotor aspects The theoretical foundation was based on issues directly related to exercises concerning the fine and gross motor skills and processes that are linked to corresponding to different authors literacy. It began with a literature research and field surveys using techniques whose data were tabulated and processed according to descriptive statistics, the analysis and interpretation of the findings and recommendations were obtained. The proposal is a simple manual to guide, with the application of different graphomotor exercises, teachers, parents and students of that school was developed.